Platinum and palladium doped tin oxide thick film sensors for sensing methane and hydrogen - Choudhary M.; Mishra V.N.; Dwivedi R. (My University, 2025)
In this work, platinum (Pt) and palladium (Pd) doped SnO 2 thick film sensors have been developed using solid state derived tin oxide powder. Thick film sensors were fabricated on a 1″ x1″ alumina substrate. The crystal structure and particle size are confirmed by X-ray diffraction (XRD) pattern. The fabricated sensors are tested for varying concentration (1-5%) of hydrogen and methane gas at different operating temperatures (200-35°C). The effect of Pt and Pd doping have been analysed on different operating temperature, sensitivity and response/recovery time. The doping effects are also very important from view point of the gas selectivity. Based on the experimental results, we have observed the formation of tetragonal structure and particle size of the powders is drastically decreases from 26 to 19 nm after replacing the platinum dopant with palladium. Both the doped sensors have been found to be sensitive for hydrogen as compare to methane however, Pd-doped SnO2 sensor are most selective for hydrogen with very fast response and recovery time (20 s, 101 s) due to the small size effect. Copyright © 2013 SPIE.